Tracheal intubation with the McGrath MAC X-blade videolaryngoscope in morbidly obese and nonobese patients - ARSLAN, Zehra Ipek (Turk J Med Sci, 2019)
BACKGROUND/AIM: Increased body mass index (BMI) and neck circumference are the two independent predictors of difficult intubation. McGrath MAC X-Blade is a videolaryngoscope specifically designed for difficult intubations. MATERIALS AND METHODS: Eighty patients with the American Society of Anesthesiologists (ASA) physical status I–III undergoing elective surgery requiring endotracheal intubation were enrolled in the study. Patients were divided into two groups, nonobese (BMI < 30) and morbidly obese (BMI > 35). All patients were intubated with the McGrath MAC X-Blade in both groups. View optimization and tube insertion maneuvers such as reinsertion of the device, slight removal of the device, cricoid pressure, handling force, 90° anticlockwise rotation of the tube, use of stylet, and head flexion maneuvers were recorded. Cormack–Lehane grades, insertion times, intubation, and total intubation times were recorded. The hemodynamic changes and postoperative minor complications were also recorded. RESULTS: Body mass index, neck circumference, Mallampati scores, and ASA physical status were statistically higher in the morbidly obese group (P < 0.001 and P < 0.05). Sternomental distances were shorter in the morbidly obese (P < 0.05). Cormack–Lehane grades were comparable among the groups. The morbidly obese patients required more reinsertion attempts and cricoid pressure maneuvers during intubation than the nonobese patients (P = 0.019 versus P = 0.012, respectively). Slight removal of the device, handling force, use of the stylet, 90° anticlockwise rotation of the tube, and head flexion maneuvers were also helpful in both groups. Although device insertion times were similar between the groups, intubation and total intubation times were longer in the morbidly obese group (P = 0.009 and P = 0.034, respectively). The groups were comparable in hemodynamic changes and postoperative minor complications. CONCLUSION: The McGrath MAC X-Blade videolaryngoscope could safely be used both in nonobese (BMI < 30) and morbidly obese (BMI > 35) patients with the aid of some key maneuvers and with a statistically significant but clinically negligible prolongation of the intubation time.